Agriculture, gendered time use, and nutritional outcomes: A systematic review - Johnston, Deborah; Stevano, Sara; Malapit, Hazel J.; Hull, Elizabeth; Kadiyala, Suneetha (International Food Policy Research Institute, 2015)
Existing reviews on agriculture and nutrition consider limited evidence and focus on impact size, rather than impact pathway. This review overcomes the limitations of previous studies by considering a larger evidence base and exploring time as one of the agriculture-nutrition pathways. Agricultural development plays a role in improving nutrition. However, agricultural practices and interventions determine the amount of time dedicated to agricultural and domestic work. Time spent in agriculture—especially by women—competes with time needed for resting, childcare, and food preparation and can have unintended negative consequences for nutrition.